1998
DOI: 10.1103/physrevb.57.r2041
|View full text |Cite
|
Sign up to set email alerts
|

Localized exciton and its stimulated emission in surface mode from single-layerInxGa1xN

Abstract: Exciton localization in In x Ga 1Ϫx N was studied. At 2 K, the time-integrated photoluminescence ͑PL͒ spectrum showed a Stokes shift from the absorption shoulder and broadening at the lower photon energy side. Site-selectively excited PL measurements determined the mobility edge. The exciton relaxation processes were studied by use of time-resolved PL spectroscopy. The PL decay time increased with the decrease of the detection-photon energy, indicating the dynamical features of exciton localization. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
68
1

Year Published

1999
1999
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(72 citation statements)
references
References 15 publications
3
68
1
Order By: Relevance
“…However, it was recently demonstrated that the reduction of dislocations can improve the lifetime of GaN-based laser diodes [2,3]. To understand this apparent contradiction, it is necessary to know not only the radiative emission mechanism of the GaInN active layer with threading dislocations [4][5][6][7], but also the optical properties of the threading dislocations themselves.…”
mentioning
confidence: 99%
“…However, it was recently demonstrated that the reduction of dislocations can improve the lifetime of GaN-based laser diodes [2,3]. To understand this apparent contradiction, it is necessary to know not only the radiative emission mechanism of the GaInN active layer with threading dislocations [4][5][6][7], but also the optical properties of the threading dislocations themselves.…”
mentioning
confidence: 99%
“…Such behavior of the luminescence band is characteristic for the localized-state filling in disordered systems. 10,11 In contrast, no considerable shifting is observed in the quaternary AlInGaN samples. We attribute the observed changes in the SSEPL to the indium-induced reduction of the band-tail states in the AlGaN sublattice.…”
mentioning
confidence: 62%
“…We attribute this shift to the carrier localization effect in the bandtail states of a partially disordered crystal. 10,12 With incorporation of In in quaternary AlInGaN layers, the spectral distribution of the decay time flattens, the peak decay time decreases, and the shift disappears. These TRL features point to a transition from a localized-to delocalized-carrier regime.…”
mentioning
confidence: 99%
“…Firstly, it has been postulated [1] that there exist localized states whose energies extend into the band gap of the InGaN QW with a density that decreases exponentially away from the band edges. In this band tail model it can be shown that the decay time increases towards lower transition energies, but the model offers no explanation for the strong dependence on well width of the decay time.…”
Section: Introductionmentioning
confidence: 99%